Microbial Diversity and Antimicrobial Resistance Profile in Microbiota From Soils of Conventional and Organic Farming Systems - Armalytė, Julija; Skerniškytė, Jūratė; Bakienė, Elena; Krasauskas, Renatas; Šiugždinienė, Rita; Kareivienė, Violeta; Kerzienė, Sigita; Klimienė, Irena; Sužiedėlienė, Edita; Ružauskas, Modestas (Frontiers in Microbiology, 2019)
Soil is one of the biggest reservoirs of microbial diversity, yet the processes that define the community dynamics are not fully understood. Apart from soil management being vital for agricultural purposes, it is also considered a favorable environment for the evolution and development of antimicrobial resistance, which is due to its high complexity and ongoing competition between the microorganisms. Different approaches to agricultural production might have specific outcomes for soil microbial community composition and antibiotic resistance phenotype. Therefore in this study we aimed to compare the soil microbiota and its resistome in conventional and organic farming systems that are continually influenced by the different treatment (inorganic fertilizers and pesticides vs. organic manure and no chemical pest management).The comparison of the soil microbial communities revealed no major differences among the main phyla of bacteria between the two farming styles with similar soil structure and pH. Only small differences between the lower taxa could be observed indicating that the soil community is stable, with minor shifts in composition being able to handle the different styles of treatment and fertilization. It is still unclear what level of intensity can change microbial composition but current conventional farming in Central Europe demonstrates acceptable level of intensity for soil bacterial communities. When the resistome of the soils was assessed by screening the total soil DNA for clinically relevant and soil-derived antibiotic resistance genes, a low variety of resistance determinants was detected (resistance to β-lactams, aminoglycosides, tetracyclin, erythromycin and rifampicin) with no clear preference for the soil farming type. The same soil samples were also used to isolate antibiotic resistant cultivable bacteria, which were predominated by highly resistant isolates of Pseudomonas, Stenotrophomonas, Sphingobacterium and Chryseobacterium genera. The resistance of these isolates was largely dependent on the efflux mechanisms, the soil Pseudomonas spp. relying mostly on RND, while Stenotrophomonas spp. and Chryseobacterium spp. on RND and ABC transporters.